SOCIAL PROTECTION IN THE INFORMAL SECTOR AND THE URBAN POOR: A CASE STUDY OF GREATER ACCRA REGION, GHANA - Quagrainie, F. A.; Adams, S.; Awunyo-Vito, D. (UDS International Journal of Development, 2019)
The objective of this study was to understand the ways in which the urban poor have their social protection needs met. The study employed an ethno survey approach, to collect data from 250 respondents. The study found that most urban poor: (1) are exposed to diverse risks but they are not well resourced to deal with these risks though many of the poor people are educated to the tertiary educational level; (2) Employed information exchange, care relations, financial protection and social activities to protect themselves against social, economic, political, and environmental risks;(3). Used coping, mitigating and prevention strategies, however about 24% of the respondents indicated that the strategies did not impact on their lives; (4. Information exchange is the most important in dealing with all the risks, followed by social activities, while financial assistance is effective in dealing with both economic and political risk; (5) Five actors -community, colleagues, friends, family, and susu - assisted the urban poor to deal with their social protection needs; (6) The most popular source of social protection is by neighbors, though the most dependable is “susu”. The key recommendation is for government to be actively involved in providing access to basic government services (for example, schools, health, roads) and setting up centers for skills training to deal with unemployment and particularly for graduate students in helping the urban poor overcome their risks. Key Words: Informal sector, Social protection, Urban poor, Development, Ghana